Nomád Pláza: három vándor . Nomad Market: Three Wanderers - Szalay, Péter (Vészi, János, 2009)
Verzio FF Duration: 00:52:00 The Roma family running a funfair, the long-distance runner flute maker and the traveling photographer – three parallel stories about the past and the present, the traditional and the modern in Hungary.